Etiology of hyperparathyroidism and bone disease during chronic hemodialysis: I. Association of bone disease with potentially etiologic factors - Fournier, Albert E.; Johnson, William J.; Taves, Donald R.; Beabout, John W.; Arnaud, Claude D.; Goldsmith, Ralph S. (The Journal of Clinical Investigation, 1971)
The present study was prompted by the observation that, in patients with chronic renal failure being followed at this center, renal osteodystrophy developed almost exclusively in those who were treated by chronic hemodialysis at home rather than in our center. A systematic comparison was made between the 10 patients with roentgenographic evidence of the bone disease and 18 patients without demonstrable bone disease. The two groups were similar in age, sex, nature of renal disease, and duration of dialysis. The mean duration of kidney disease was almost 2 yr longer in the patients without bone disease than in those with bone disease. Other significant differences related to where the hemodialysis was performed and to the calcium concentration in the dialysate (6.0-7.4 mg/100 ml in the hospital and 4.9-5.6 mg/100 ml at home). If the unknown factors related to where the dialysis was performed were of no consequence, the major factor contributing to the production of bone disease observed in these patients was the use of a dialysate with a calcium concentration less than 5.7 mg/100 ml.